menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve the following for y: 9x − 3y = 18 y = −3x − 6 y = 3x − 6 y = −3x + 6 y = 3x + 6
asked
Mar 9, 2019
15.3k
views
4
votes
Solve the following for y: 9x − 3y = 18
y = −3x − 6
y = 3x − 6
y = −3x + 6
y = 3x + 6
Mathematics
high-school
Jacob Fike
asked
by
Jacob Fike
5.3k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
4
votes
Y=3x-6 is the right answer
Kage
answered
Mar 11, 2019
by
Kage
4.9k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
2
votes
the answer is B.......
Arturski
answered
Mar 16, 2019
by
Arturski
5.8k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.8m
questions
7.5m
answers
Other Questions
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Find the quotient of 3,078 ÷ 27. A) 104 B) 109 C) 114 D) 119
Solve for h 3h=7(2/7-3/7h)-10
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org